Hemidesmosomes modulate force generation via focal adhesions - Wang, Wei (J Cell Biol, 2020)
Hemidesmosomes are specialized cell-matrix adhesion structures that are associated with the keratin cytoskeleton. Although the adhesion function of hemidesmosomes has been extensively studied, their role in mechanosignaling and transduction remains largely unexplored. Here, we show that keratinocytes lacking hemidesmosomal integrin α6β4 exhibit increased focal adhesion formation, cell spreading, and traction-force generation. Moreover, disruption of the interaction between α6β4 and intermediate filaments or laminin-332 results in similar phenotypical changes. We further demonstrate that integrin α6β4 regulates the activity of the mechanosensitive transcriptional regulator YAP through inhibition of Rho–ROCK–MLC– and FAK–PI3K–dependent signaling pathways. Additionally, increased tension caused by impaired hemidesmosome assembly leads to a redistribution of integrin αVβ5 from clathrin lattices to focal adhesions. Our results reveal a novel role for hemidesmosomes as regulators of cellular mechanical forces and establish the existence of a mechanical coupling between adhesion complexes.